Proportion of Meat, Bone and Fleshing Index of Bali Cattles at Age 2 to 5 Years - Harapin Hafid; N.S. Asminaya (Talenta Publisher, 2020)
Bali cattle (Bossondaicus,Bosjavanicus,Bos/Bibos Banteng) are one of Indonesia's native livestock genetic resources that greatly contribute to the development of the livestock industry in Indonesia The purpose of this study was to compare the proportions of meat, bone and fleshing index of Bali cattles at different ages. This research was conducted in Kendari City Slaughterhouse by observing the slaughter of 89 cattles. The results showed that Bali cattles at different ages showed a significant effect (P <0.05) on the proportion of meat, bones, and fleshing index. It can be concluded that the age of cattles is directly proportional to meat production. Cattles with 5 years of age have a maximum meat content of 27.22% and bones of at least 18.61%, while in terms of fleshing index Bali cattles aged 4 years have the highest fleshing